2017
DOI: 10.1159/000477347
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Real-Time Assessment of Liver Function with Near-Infrared Fluorescence Imaging

Abstract: Background: Postoperative liver failure is a serious complication after major hepatectomy, and perioperative prediction of its incidence using current technology is still very difficult. Near-infrared (NIR) fluorescence imaging allows quantitative assessment of the fluorescent signal from indocyanine green (ICG) in regions of interest on the liver surface. This method might offer a new promising modality for evaluating regional liver reserve. However, data are lacking regarding the relationship between liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Quantitative assessment of the global hepatic function using this imaging technique was only reported by Narasaki et al ( 13 ) They reported that the FI on the liver surface was not correlated with the global hepatic function measured by plasma clearance rate of indocyanine green (ICGK) at 15 minutes. This lack of correlation resulted from an interindividual variability in factors that can influence FI by absorption and scattering of NIR fluorescent light, such as the presence of liver steatosis or fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Quantitative assessment of the global hepatic function using this imaging technique was only reported by Narasaki et al ( 13 ) They reported that the FI on the liver surface was not correlated with the global hepatic function measured by plasma clearance rate of indocyanine green (ICGK) at 15 minutes. This lack of correlation resulted from an interindividual variability in factors that can influence FI by absorption and scattering of NIR fluorescent light, such as the presence of liver steatosis or fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, this parameter was measured for only a few seconds during LT, and the consequence of some possible biases, such as hemodynamic instability or the possible effects of anesthetic agents during general anesthesia, are not yet known on the pharmacokinetics of ICG. ( 13 ) For this reason, all measurements were performed on hemodynamically stable patients (pressor amines permitted) because severe instability, being itself a risk factor for PNF, could bias ICG interpretation. Second, the indication for re‐LT is a serious decision with severe consequences for the patient with higher morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of near-infrared fluorescence (NIRF) imaging might be able to meet this need. This technique is already used in hepatobiliary surgery to visualize the bile ducts [8] or the perfusion of the liver [9], and in colorectal surgery to assess the perfusion of the bowel anastomosis [1015]. A few studies have also been published on the use of NIRF imaging to identify the ureters.…”
mentioning
confidence: 99%